الجرائم المرتکبة بحق الإیزیدیین في ضوء النظام الأساسي للمحکمة الجنائیة الدولیة - گول, معروف عمر; درویش, دلپاك طاهر (Sulaimani Journal for Humanities, 2021)
In our research entitled (crimes against the Yezidis in light of the statute of the International Criminal Court), international crimes and the jurisdiction of the International Criminal Court were covered, in addition to how the case was initiated in the statute of the court itself. By relying on the rules specified in the Basic Law, we were able to study the basic aspects of the contents of the topic in order to reach the conclusion that the practices carried out by the terrorist organizations of ISIS have reached the level of international crimes. Including the crime of genocide, because the crimes committed resulted in unnatural and dangerous situations against the Yazidi component. International crimes in the statute of the International Criminal Court depend on the nature of the court's jurisdiction and how the case is initiated. With regard to the jurisdiction of the court, the statute of the court affirmed the four specializations: spatial, temporal, personal, and substantive. Under these jurisdictions, the court can practice its judicial work. In addition, to initiate a lawsuit by virtue of the statute of the court, the case is referred by: - The UN Security Council, according to the powers of the Council in accordance with Chapter Seven of the United Nations Charter. - The authority of the public prosecutor on his own initiative, according to Article 15 of the Court's Statute. - States Parties (members) of the Court. - The authority of states not parties to the court, in accordance with the principle of complementarity, in the event that the national judiciary is unable to consider a case, if it falls within the jurisdiction of the International Criminal Court. Moreover, international crimes and their pillars in the statute of the International Criminal Court have been dealt with according to their classification for each type and the nature of its elements. The types of international crimes stipulated in the Basic Law are embodied in the crime of genocide, crimes against humanity, war crimes and crimes of aggression. The statute of the court has established the elements of international crimes with the legal element, the international element, the material element and the moral element. Therefore, the study was divided into two main sections as follows: The first topic: International crimes in the statute of the International Criminal Court. In this section, the subject was studied in two requirements: the first under the title of the International Criminal Court's jurisdiction, and the second request under the title Mobilization of the case in the Statute of the International Criminal Court. As for the second topic: Types of international crimes and their elements in the statute of the International Criminal Court, and this topic includes two requirements, as follows: The first requirement: the types of international crimes in the statute of the International Criminal Court, and the second requirement: the elements of international crimes in the statute of the International Criminal Court.